Corporate tax burden and financial attributes of fraud firms and non-fraud firms / Ainon Mardia Mohamed Yusof, Rohaya Md Noor and Mohamad Ridhuan Mat Dangi - Mohamed Yusof, Ainon Mardia; Md Noor, Rohaya; Mat Dangi, Mohamad Ridhuan (Universiti Teknologi MARA Cawangan Pahang, 2014)
The goal of this study was to examine corporate tax burdens and the financial attributes of fraud firms (FF) and non-fraud firms (NFF) in Malaysia. This study used the company’s effective tax rate (ETR) to determine the level of corporate tax burden. The sample of fraud firms was obtained from the Enforcement Release reported by the Securities Commissions focusing on criminal prosecutions from the year 2001 to 2010. The fraud firms were then matched with the non-fraud firms on the basis of size, time period and industry. The investigation period of this study covered a period of four years, i.e., a fraud year and the three years prior to the companies being prosecuted for fraud. Using a total of 264 firm-years from 33 fraud firms and 33 non-fraud firms, this study examined the level of corporate ETR, the variation of corporate ETR from Statutory Tax Rate (STR), and the association between companies’ financial attributes and their ETR. Five financial attributes were examined; firm size, leverage, return on assets, capital intensity and inventory intensity. The statistical results revealed that both the mean ETR for fraud firms (50.14%) and non-fraud firms (36.07%) were higher than the mean STR (27.67%) imposed by the government during the period under study. The findings indicate that fraud firms paid higher tax expense than the non-fraud firms. Further, the findings also indicate that return on assets and capital intensity were significantly associated with the variability of the corporate ETR. The study has provided empirical evidence that both fraud firms and non-fraud firms paid higher effective tax rate than the statutory tax rate. Thus, the findings imply that the sample fraud firms were not tax-motivated. Hence, the study has contributed to the tax literature on the financial attributes of fraud firms which could assist relevant authorities, specifically in selecting cases for the tax audit and investigation.